Template‐Free Electrodeposition of Zinc Nanowires from an Ionic Liquid. Issue 9 (1st June 2015) - Pulletikurthi, Giridhar; Shapouri Ghazvini, Maryam; Prowald, Alexandra; Zein El Abedin, Sherif; Endres, Frank
Abstract The template‐free synthesis of zinc nanowires was achieved from Zn(TfO)2 in 1‐butyl‐1‐methylpyrrolidinium trifluoromethylsulfonate ([Py1, 4]TfO) at 125 °C. The electrodeposition process was evaluated by using cyclic voltammetry. The electrodeposited zinc was characterized by using scanning electron microscopy (SEM) and X‐ray diffraction. SEM images indicated that the zinc deposits on gold contain nanowires of varying lengths, ranging from approximately 400 nm to 1.2 μm, whereas intertwined nanowire structures were observed on indium tin oxide (ITO) from the same solution. A similar kind of intertwined nanowire structure was also observed on both gold and ITO from ZnCl2/[Py1, 4]TfO at the same temperature. The results show that zinc nanowire structures can be achieved from ionic liquids without a template at elevated temperatures.